Socio-demographic determinants of unmet need for family planning among married women in Pakistan - Muhammad Farhan Asif; Zahid Pervaiz (BMC, 2019)
Abstract Background Family planning is considered as an effective tool to control population and to bring improvement in maternal and child health. The Government of Pakistan has been continuously struggling to improve the availability of family planning services. However, like many other developing countries of the world, unmet need for family planning still exists in the country. According to Pakistan Demographic and Health Survey 2012-13, the prevalence of unmet need for family planning is 21% in the country. The objective of this study is to investigate the determinants of unmet need for family planning among married women in Pakistan. Methods Secondary data of Pakistan Demographic and Health Survey 2012-13 has been used to analyze the determinants of unmet need for family planning through Binary and Multinomial Logistic regressions. Results Outcomes of the study show that the likelihood of unmet need for family planning among married women in Pakistan goes on to decrease with an increase in their age and education. The likelihood of unmet need for family planning decreases with the increase in wealth status of women's household, number of living children and husband's education. Similarly, the women residing in rural areas are more likely to have unmet need for family planning as compared with women living in urban areas. The women who lack mass media exposure, who are not employed and who have fear of side effects for using contraceptives are more likely to have unmet need for family planning. Conclusions Fear of side effects for using contraceptives has been identified as the major cause of unmet need for family planning in Pakistan. The Government of Pakistan has been putting a lot of efforts to convince people about the usefulness of population control programs. A huge media campaign has been launched to persuade people about the benefits of birth control. But the efforts of the government do not seem to be very much effective to clear the perception of people about side effects of contraceptive use. Hence, fear of side effects still remains one of the most important reason behind unmet need for family planning.